Quick fix - Poh, Ying Xin (2015)
Katie is a social worker who struggles with the demands of her busy life, juggling her patients, her demanding boss and her personal life. She steals medication from her patients at the hospice where she works and uses them to cope with the stress of life. Jake is an air-con service man who had injured his back at work and goes to Katie for help with his medical claims. While Jake was waiting at Katie’s office one day, he discovers Katie’s stash of stolen drugs. When Katie is assured that he will keep her secret, the two develop a closer relationship, blurring the lines between patient and social worker. Jake’s condition worsens and Katie is then faced with the dilemma of providing him with medicine without a prescription and reevaluate her own drug use.